Implementation of Human Resource Management and The Harmony of Organizational Culture - Kristian, Indra (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
Human resources are widely recognized as a crucial factor in achieving organizational success. Therefore, it is essential to implement systematic and comprehensive human resource management. Many success stories demonstrate how developed countries have effectively developed and implemented human resource management practices. This article outlines steps for successfully adopting these best practices in developing countries. To achieve organizational success, it is necessary to overcome cultural differences between developed and developing countries. This can be achieved through interventions aimed at minimizing constraints from the social environment. Efforts should include shifting cultural boundaries and aligning cultural beliefs and values with management techniques and practices within the local culture. Consistency in applying these efforts is crucial.